2008
DOI: 10.1016/j.jiph.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carriage rate of Streptococcus pneumoniae in children with sickle cell disease before and after the introduction of heptavalent pneumococcal conjugate vaccine

Abstract: Children with sickle cell disease (SCD) are at high risk of severe infection with Streptococcus pneumoniae (SP). From 2002, all children aged <5 years in the UK with SCD were recommended 7-valent pneumococcal conjugate vaccine (PCV-7) in infancy and 23-valent pneumococcal polysaccharide vaccine boosting, in addition to regular penicillin prophylaxis. Our objective was to determine the nasopharyngeal (NP) carriage rate of SP in children aged <5 years with SCD before and after vaccination with PCV-7 (by vaccine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[ 25 ] among SCD children ≤5 years in Kumasi (a city in Ghana) reported a pneumococcal carriage prevalence of 16%, which is much lower than the prevalence (47.9%) observed among the same age group in the current study. Pneumococcal carriage prevalence among children with SCD reported in other countries were 33% in Uganda [ 26 ], 14% in Gabon [ 27 ], 13% in the USA [ 28 ] and 21% in the UK [ 29 ]. In Ghana, the relatively higher prevalence of pneumococcal carriage observed among SCD children in this study could be partly due to the small proportion of 7% who were on penicillin prophylaxis compared to over 50% in the study of Donkor et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] among SCD children ≤5 years in Kumasi (a city in Ghana) reported a pneumococcal carriage prevalence of 16%, which is much lower than the prevalence (47.9%) observed among the same age group in the current study. Pneumococcal carriage prevalence among children with SCD reported in other countries were 33% in Uganda [ 26 ], 14% in Gabon [ 27 ], 13% in the USA [ 28 ] and 21% in the UK [ 29 ]. In Ghana, the relatively higher prevalence of pneumococcal carriage observed among SCD children in this study could be partly due to the small proportion of 7% who were on penicillin prophylaxis compared to over 50% in the study of Donkor et al .…”
Section: Discussionmentioning
confidence: 99%
“…Carriage rates of S. pneumoniae among children with HbSS disease reported in other countries were 33% in Uganda,7 14% in Gabon,8 13% in the USA,26 and 21% in the UK 27. S. pneumoniae carriage among subjects with HbSS disease in the current study (10%) is similar to a carriage rate of 16% previously reported among HbSS disease children in Ghana,6 but significantly lower than most of the carriage rates (>40%) that have been reported generally among children in Ghana 28,29.…”
Section: Resultsmentioning
confidence: 81%
“…24,25,47,49 Finally, 1 study among Australian Aboriginal children showed a significant reduction in VT carriage following a 3+1PPV23 schedule, 36 while a British study among children with sickle cell disease found a nonsignificant reduction in VT carriage following a 3+1PPV23 schedule. 26 …”
Section: Resultsmentioning
confidence: 99%